Tense shifts in science-fiction discourse - Mňoučková, Veronika (Univerzita Pardubice, 2020)
This bachelor thesis analyses various forms of direct, indirect and semi-direct speech and examines the use of tense shifts in science fiction discourse. The theoretical part briefly introduces the English system of verb tenses. Furthermore, the above-mentioned forms of speech and their specifics are defined, including the conditions under which backshift is applied or not. Finally, a science fiction discourse is introduced. The analytical part of this thesis deals with the occurrences of indirect discourse and works with excerpts selected from dystopian themed books. The analysis focuses specifically on the frequency of occurrence of individual forms of reported speech and on the reasons for application or non-application of backshift.
Časová souslednost v diskurzu science fiction
Keywords: slovesný čas; polopřímá a nepřímá řeč; časová souslednost; diskurs science fiction; tense; reported speech - indirect speech/free indirect soeech; free direct/indirect speech; backshift; discourse science - fiction